The frequency of intraocular hemorrhage in hereditary vitreoretinal dystrophies - O. Yu. Yatsenko; O. S. Velibekova (Российский офтальмологический журнал, 2018)
Hereditary vitreoretinal degenerations are a heterogeneous group of diseases, which are based on the degenerative changes of the retina and the vitreous. The occurrence of intrahemorrhages is different for different hereditary vitreoretinal degenerations. In some diseases (Wagner's disease, Jensen syndrome, Kniest dysplasia, Marfan's, Ehlers -Danlos syndrome, Alport, Bloch -Sulzberger, Walker -Warburg) intraocular hemorrhages almost never occur. In other vitreoretinopathies (X-linked congenital retinoschisis, familial exudative vitreoretinopathy, Norrie disease, Stickler syndrome), intraocular hemorrhages occur more often. The review describes the genetic aspects of the diseases and their clinical pictures. Special attention is given to the incidence and clinical manifestations of intraocular hemorrhage in the above mentioned vitreoretinopathies // Russian Ophthalmological Journal, 2017; 1: 104-10. doi: 10.21516/2072-0076-2017-10-1-104-110.